A murder over a girl : justice, gender, junior high - Corbett, Ken (Henry Holt and Co., 2016)
"A psychologist's gripping, troubling, and moving exploration of the brutal murder of a possibly transgender middle school student by an eighth grade classmate. On Feb. 12, 2008, at E.O. Green Junior High in Oxnard, CA, 14-year-old Brandon McInerney shot and killed his classmate, Larry King, who had recently begun to call himself "Leticia" and wear makeup and jewelry to school. Profoundly shaken by the news, and unsettled by media coverage that sidestepped the issues of gender identity and of race integral to the case, psychologist Ken Corbett traveled to LA to attend the trial. As visions of victim and perpetrator were woven and unwoven in the theater of the courtroom, a haunting picture emerged not only of the two young teenagers, but also of spectators altered by an atrocity and of a community that had unwittingly gestated a murder. Drawing on firsthand observations, extensive interviews and research, as well as on his decades of academic work on gender and sexuality, Corbett holds each murky facet of this case up to the light, exploring the fault lines of memory and the lacunae of uncertainty behind facts. Deeply compassionate, and brimming with wit and acute insight, A Murder Over a Girl is a riveting and stranger-than-fiction drama of the human psyche"--